THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL, DIVIDEND POLICY, PROFITABILITY RATIO AND ACTIVITY RATIO ON COMPANY VALUE - Tri Astuti; Sri Ambarwati; Frides Dyah Wibowo (FEB-UP Press, 2022)
Abstractk This study aims to determine the effect of green intellectual capital, dividend policy, profitability ratios and activity ratios on firm value. This study takes a sample of companies listed on the Indonesia Stock Exchange which are included in the Sri-KEHATI Index list for the 2016-2020 period. The sample in this study a sample of 9 companies with a total of 45 observations of observation data for 5 years. A total of 5 outlier data have been removed from the analysis so that the total observations are 40 observational data. The data analysis method used is panel data regression with the help of the Eviews 9 program. The results show that partially green intellectual capital, dividend payout ratio and return on equity have no effect on firm value.